Azimuthal Anisotropy of the Crust and Uppermost Mantle Beneath Alaska. Issue 12 (25th December 2020) - Feng, L.; Liu, Chuanming; Ritzwoller, M. H.
Abstract: This study presents an azimuthally anisotropic shear wave velocity model of the crust and uppermost mantle beneath Alaska, based on Rayleigh wave phase speed observations from 10 to 80 s period recorded at more than 500 broadband stations. We test the hypothesis that a model composed of two homogeneous layers of anisotropy can explain these measurements. This "Two‐Layer Model" confines azimuthal anisotropy to the brittle upper crust along with the uppermost mantle from the Moho to 200 km depth. This model passes the hypothesis test for most of the region of study, from which we draw two conclusions. (a) The data are consistent with crustal azimuthal anisotropy being dominantly controlled by deformationally aligned cracks and fractures in the upper crust undergoing brittle deformation. (b) The data are also consistent with the uppermost mantle beneath Alaska and surroundings experiencing vertically coherent deformation. The model resolves several prominent features. (1) In the upper crust, fast directions are principally aligned with the orientation of major faults. (2) In the upper mantle, fast directions are aligned with the compressional direction in compressional tectonic domains and with the tensional direction in tensional domains. (3) The mantle fast directions located near the Alaska‐Aleutian subduction zone and the surrounding back‐arc area form a toroidal pattern that is consistent with mantle flow directions predicted by recent geodynamical models. Finally, the mantle anisotropy is remarkably consistent with SKS fast directions, but to fit SKS split times, anisotropy must extend below 200 km depth across most of the study region. Key Points: An azimuthally anisotropic shear wave velocity model of Alaska is constructed from Rayleigh wave dispersion data Crustal anisotropy reflects the orientation of major faults across Alaska Mantle anisotropy is consistent with SKS splitting directions, revealing a toroidal pattern of fast directions around the Alaskan subduction zone